2016
DOI: 10.1088/2057-1976/2/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

Optimum absorbed dose versus energy response of Gafchromic EBT2 and EBT3 films exposed to 20–160 kV x-rays and 60 Co gamma

Abstract: High-accuracy in the absorbed-dose and small energy-dependence are important features of a dosimeter to be considered ideal for medical applications. This work investigated the relation between the optimum absorbed-dose in terms of combined standard-uncertainty and energyresponse of EBT2 and EBT3 films exposed to five x-ray beams and 60 Co. A systematic analysis was performed to control the fitting procedure in order to find the parameter-values that best describe the experimental data. Six EBT2 and three EBT3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…This was done to avoid scattering radiation from the acrylic material to the beam centre. Based on the results recently reported, the absorbed dose delivered to the film in the Cyberknife was around 10 Gy at dmax and analysed in the green channel in order to decrease the combined standard uncertainty [9], which was confirmed from the uncertainty analysis made in this work. All the results were compared with that measured with an IBA stereotactic field diode (SFD).…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…This was done to avoid scattering radiation from the acrylic material to the beam centre. Based on the results recently reported, the absorbed dose delivered to the film in the Cyberknife was around 10 Gy at dmax and analysed in the green channel in order to decrease the combined standard uncertainty [9], which was confirmed from the uncertainty analysis made in this work. All the results were compared with that measured with an IBA stereotactic field diode (SFD).…”
Section: Methodssupporting
confidence: 78%
“…The films were cut into pieces of 1.2 cm x 1.2 cm for the calibration and of 7 cm x 25.4 cm for the measurements in the Cyberknife and scanned 24 hours pre-and post-irradiation according to our protocol reported elsewhere [9]. The reading process was made using an EPSON 11000-XL document flatbed scanner at 300 dpi spatial-resolution and 48-bit colour depth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For doses higher than 1 Gy, no significant statistical differences were found between 6 and 15 MV and only small differences (11%) were detected when comparing the 50 kV beam with the megavoltage ones. The same authors also found a slight energy dependence of EBT3 when exposing them to low energy X‐rays (between 20 and 160 kV) compared to Co‐60 irradiations . Sorriaux et al determined calibration curves for EBT3 films for five different beams, namely 6 and 18 MV photon, 60 and 100 MeV proton, and 6 MeV electron beams.…”
Section: Introductionmentioning
confidence: 96%
“…Gafchromic™ films have lots of advantages and they are broadly utilized in radiotherapy; for example, verifying treatment planning systems, evaluating two-dimensional ambient absorbed dose, and investigating dose distribution in small radiotherapy fields. [4] The EBT and EBT2 films are typical types of Gafchromic™ films which are used in radiation therapy quality assurance (QA) and have several important advantages including better spatial resolution, energy and dose rate independency, effective atomic number and a density close to the soft tissue or water, lower sensitivity to room light (resulting in easy handling), and low postirradiation growth. [567] In addition, these films are self-developing; therefore, they do not need the conventional chemical processing[6] and also, they can be shaped to fit in any phantom.…”
Section: Introductionmentioning
confidence: 99%